Penerapan Manajemen Persediaan Dan Total Quality Management Terhadap Kinerja Operasional - Hafizh Reyhan Yafi; Choirum Rindah Istiqaroh; Mintarti Indartini; Handaru Agnyana (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
The aim of this study is to examine the influence of Inventory Management and Total Quality Management on the Operational Performance of PT Sinergi Gula Nusantara PG. Poerwodadie The sampling technique used in this research is purposive sampling method. The data was obtained from primary data collected through questionnaires distributed to the employees of PT Sinergi Gula Nusantara PG. Poerwodadie. The data analysis was conducted using multiple linear regression with SPSS version 26.00 for windows. The results of the hypothesis testing indicate that the independent variable Inventory Management has a coefficient of 7.037, while the independent variable Total Quality Management has a coefficient of 9.012. Based on these results, it can be concluded that Inventory Management and Total Quality Management have a significant positive influence on the Operational Performance of PT Sinergi Gula Nusantara PG. Poerwodadie.